Pengaruh Kurs, NIM dan NPL terhadap Nilai Perusahaan Perbankan di Indonesia: - Mahardika, Dewa Putra Krishna; Anjalani, Lala (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Firm value is the dependent variable in this study. The value of companies in the banking industry has decreased in 2021, this is due to falling stock prices in the banking industry. Corporate value is something that is very important to establish and maintain, in order to make shareholders or investors feel safe. This study aims to determine the effect of exchange rates, NIM, and NPL on the value of banking companies listed on the IDX (2018 – 2021). Using quantitative descriptive with secondary data in the form of financial reports on the Indonesian Stock Exchange (IDX). Companies on the IDX for the 2018-2021 period are population and purposive sampling technique, resulting in 108 samples consisting of 45 companies with an observation period of 4 years. This study was analyzed using panel data regression. Keywords: kurs, net interest margin, non-performing loans, company value.